Student learning motivation in following practice theory floor gymnastics learning at undiksha penjaskesrek study program - Rizky Suhartono; I Gede Suwiwa; I Ketut Budaya Astra (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
This study aims to determine student motivation for TP floor gymnastics learning in the Undiksha Penjaskesrek study program during the even semester of 2021-2022. This study is quantitative descriptive research in the form of a survey. The population in this study were all students in the Physical Education Study Program who attended TP lectures. The total number of floor gymnastics lessons for 2021–2022 is 114. The sample selection method used total sampling, i.e., the population became the research sample, so the number of samples in this study was 114. The data analysis technique used quantitative descriptive statistics with interval categories. The results of this study are the intrinsic factors of student learning motivation in following the TP. Floor gymnastics learning gets a value of 70.76% if it is converted into a category interval included in the high category. While the intrinsic factors of student learning motivation in following the TP receives a value of 70.4% when converted into a category interval included in the high category, floor gymnastics learning receives a value of 70.4% when converted into a category interval included in the high category. Students learn motivation by following the TP. Floor gymnastics learning in the Undiksha Penjaskesrek study program in the even semester of 2021/2022 will be 68.5% based on the two indicators on the variable. When converted into category intervals, student motivation for floor gymnastics learning falls into the high category. Thus, students of the Undiksha Penjaskesrek study program are advised to maintain and increase motivation in participating in the TP floor gymnastics learning in the Undiksha Penjaskesrek study program in the even semester of 2021/2022.